Carlos Luis Fallas Sibaja y la crítica académica: la configuración de un escritor canónico nacional (1966-2011) - Castillo Rodríguez, Larissa (2024)
This article analyzes the process of canonization or public institutionalization of the Costa Rican writer Carlos Luis Fallas Sibaja in the period 1966-2011. To study this process, a sample of the academic criticism that was produced about him is used. First, there is a section addressing bibliographical research on Fallas. Second, a section about publications, which pointed out the autobiography of 1957 as a text of significant importance to analyze the relevance of Fallas’s literary material in the national context. Third, there will be a reference to the academic tributes granted to this writer in two Costa Rican journals, to the studies carried out based on thetranslation of his novels, and, finally, a short reference to the paratexts of his literary work.